Partial restoration of gut‐mucosal dysbiosis in late‐treated HIV‐infected subjects with CD4 T‐cell recovery - Olivas‐Martínez, Israel; Rosado‐Sánchez, Isaac; Cordero‐Varela, Juan Antonio; Sobrino, Salvador; Genebat, Miguel; Herrero‐Fernández, Inés; Pablos, Rocío Martínez; Carvajal, Ana Eloísa; Ruiz, Rocío; Isabel Álvarez‐Ríos, Ana; Fontillón‐Alberdi, María; Bulnes‐Ramos, Ángel; et al. (Clinical and translational medicine, 2022)
[...]we aimed to explore potential differences in specific dysbiosis in the gut-mucosal microbiome, comparing biopsies from two different locations (ileum and caecum), of HIV-infected subjects with different clinical phenotypes. SEE PDF] Sequencing data of 16S rRNA from the microbiota present in terminal ileum and caecum samples of study subjects were analysed and compared with bacterial taxonomic databases. [...]parameters of richness and alpha-diversity of the gut microbiome showed no statistically significant differences between healthy and HIV-groups (elite controller [EC], early-treated [ET], late-treated high recovery [LT-HR] and late-treated low recovery [LT-LR]) regardless the biopsied intestinal area (Figure 2A) or patient sex (Figure S1). [...]abundance analyses were performed without separating by gut location. [...]this is the first report to analyse the potential association of the clinical phenotype of HIV-subjects, regarding their CD4 status at cART onset and afterwards, with alterations in the microbiome composition.